2023
DOI: 10.3390/jpm13050746
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Management for Heart Failure with Preserved Ejection Fraction

Abstract: Heart failure with preserved ejection fraction (HFpEF) is a heterogeneous clinical syndrome with multiple underlying mechanisms and comorbidities that leads to a variety of clinical phenotypes. The identification and characterization of these phenotypes are essential for better understanding the precise pathophysiology of HFpEF, identifying appropriate treatment strategies, and improving patient outcomes. Despite accumulating data showing the potentiality of artificial intelligence (AI)-based phenotyping using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The first research group to attempt this ambitious goal was that of Shah et al, who identified patient subgroups based on their comorbidities, including those related to obesity, metabolic syndrome and pulmonary hypertension. 11,21 More recently, Uijil et al proposed a model consisting of five clusters obtained from HFpEF patients recorded in the Swedish Heart Failure Registry, and validated it externally with the Chronic Heart Failure European Society of Cardiology guideline-based Cardiology Practice Quality project registry. 18 The first cluster is that of young patients, with an average age <60 years and a reduced burden of comorbidities, including arterial hypertension and obesity.…”
Section: Hfpef Phenotypes: Pieces Of a Complex Clinical Puzzlementioning
confidence: 99%
See 1 more Smart Citation
“…The first research group to attempt this ambitious goal was that of Shah et al, who identified patient subgroups based on their comorbidities, including those related to obesity, metabolic syndrome and pulmonary hypertension. 11,21 More recently, Uijil et al proposed a model consisting of five clusters obtained from HFpEF patients recorded in the Swedish Heart Failure Registry, and validated it externally with the Chronic Heart Failure European Society of Cardiology guideline-based Cardiology Practice Quality project registry. 18 The first cluster is that of young patients, with an average age <60 years and a reduced burden of comorbidities, including arterial hypertension and obesity.…”
Section: Hfpef Phenotypes: Pieces Of a Complex Clinical Puzzlementioning
confidence: 99%
“…Excess visceral adipose tissue promotes the hyperactivation of neurohormonal systems that, together with the reduced plasma activity of neprilysin typical of these patients, make the pro-inflammatory and fibrotic effect of aldosterone unopposed, favouring diastolic dysfunction that is responsible for the progressive increase in filling pressures. 21 Considering the typical pathophysiological changes of the obese phenotype, RAASi, particularly aldosterone antagonists and neprilysin inhibitors (ARNI), play a central role, in addition to the use of SGLT2i. Furthermore, the STEP-HFpEF trial has recently demonstrated in obese HFpEF patients that semaglutide versus placebo significantly reduced body weight, improving symptoms, physical limitations and exercise function, with a positive impact on quality of life (QoL), inflammatory status and survival.…”
Section: Hfpef Phenotypes: Pieces Of a Complex Clinical Puzzlementioning
confidence: 99%
“…One widely acknowledged HFpEF mechanism is chronic inflammation caused by co-occurring conditions [ 10 , 14 ]. These diseases cluster together to form specific phenotypes, offering further guidance on treatment [ 15 , 16 , 17 ]. Because HFpEF is notoriously known for non-cardiovascular mortality, apart from SGLT2 inhibitor, other therapies are often required to optimize comorbid conditions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%